2020
DOI: 10.17268/agroind.sci.2020.01.14
|View full text |Cite
|
Sign up to set email alerts
|

Garlic (Allium sativum L) and Its beneficial properties for health: A Review

Abstract: Generally, chefs use garlic as an ingredient that enhances the sensory qualities of foods. However, recent studies have shown that garlic contains Sulphur compounds, which provide a health benefit. This review identifies and describes those constituents in garlic responsible for their anti-microbial, antioxidant, anti-inflammatory, and in some cases anti-cancer properties. Also, this review reports the chemical and nutritional contents of garlic (Allium sativum L.) and shows its health benefits for humans. A l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 101 publications
(130 reference statements)
0
5
0
Order By: Relevance
“…Heart disease is considered to be one of the biggest causes of death worldwide, which includes heart-related diseases like hypertension. Studies have shown that garlic can help people who are suffering from hypertension by lowering their blood pressure ( 91 ). By partially increasing Na+/K+-ATPase levels, garlic and its identified metabolites can inhibit iso-induced hypertrophic development in rat heart tissue and H9C2 cell lines ( 92 ).…”
Section: Health Benefits Of Garlicmentioning
confidence: 99%
“…Heart disease is considered to be one of the biggest causes of death worldwide, which includes heart-related diseases like hypertension. Studies have shown that garlic can help people who are suffering from hypertension by lowering their blood pressure ( 91 ). By partially increasing Na+/K+-ATPase levels, garlic and its identified metabolites can inhibit iso-induced hypertrophic development in rat heart tissue and H9C2 cell lines ( 92 ).…”
Section: Health Benefits Of Garlicmentioning
confidence: 99%
“…The antibacterial activity of the aqueous Allium sativum extract on three standard organisms studied varies with the type and composition of the extract, concentration used, types of microorganism, pH value and temperature of the environment [38]. The results of this study indicated that the aqueous extract of garlic had an antibacterial activity on the tested organisms.…”
Section: Discussionmentioning
confidence: 71%
“…Fresh garlic bulbs have been found to contain roughly 0.4% allicin and 0.9% alliin. Alliin is the main sulfur compound in both raw and powdered garlic, with about 8 g/kg present in garlic cloves (Espinoza et al, 2020). Allicin can compromise bacterial cell walls by destabilizing the peptidoglycan layer, leading to cell shrinkage, swelling, and eventual lysis.…”
Section: Allicin (S-allyl-2-propene Thiosulfinate)mentioning
confidence: 99%
“…Ajoene is a collection of various organosulfur compounds that are associated with the properties of garlic. Chemically identified as (E, Z)-4,5, 9-trithiadodeca-1, 6, 11-triene 9-oxide, ajoene remains stable in water (Espinoza et al, 2020). Derived from three allicin molecules, both types of ajoene undergo this conversion (Nakamoto et al, 2020).…”
Section: Ajoene (E-ajoene Z-ajoene)mentioning
confidence: 99%